A missional reflection on the challenges of getting married faced by the poor: A case study from Soshanguve - Kabongo, Kasebwe T. L. (HTS teologiese studies, 2020)
This is a case study that is written from the perspective of a black African who lives in a community of poverty. He has observed a growing number of adults who desire to get married, but only cohabit. He formed a focus group with five cohabiting couples who desired to get married. Through this focus group, they discussed impediments of getting married as well as alternatives for converting challenges to resources that would make marriage a reality. A mission practitioner who values being a tangible sign of hope through involvement in social matters catalysed the happenings of this case study through a group he put together. The results of the focus group reveal stories of both success and failure.